Land encroachment: India's disappearing common lands - Robinson, E (2004)
Opportunistic land encroachment, resulting from costly and incomplete enforcement of common land boundaries, is a problem in many less-developed countries. A multi-period model of such encroachment is presented in this paper. The model accounts explicitly for the cumulative effects of non-compliance of regulations designed to protect a finite, non-renewable resource - in this case common land - from private expropriation. Gradual evolution of property rights from common to private - the consequence of encroachment - is demonstrated to be an equilibrium. To prevent the complete loss of common land, full enforcement must be the rule rather than the exception.